DETERMINANTS OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) DISCLOSURE - Aya Husein Hasan Abdelhaq (جامعة النجاح الوطنية, 2025)
This study investigates the determinants of Sustainable Development Goals (SDG) disclosure among European listed firms, emphasizing the combined influence of corporate governance characteristics and firm-specific financial factors. Using a purposive sample of 1,886 companies from both financial and non-financial sectors over the period 2019–2022, the research examines the effect of board size, board gender diversity, CSR committee presence, leverage, firm size, return on assets (ROA), and ESG performance on the extent of SDG-related reporting. SDG disclosure is measured as the proportion of the 17 United Nations goals addressed by each firm. Regression analysis results indicate that board size, CSR committee presence, firm size, ROA, leverage, and ESG performance are significant determinants of SDG disclosure, while board gender diversity shows no statistically significant effect. These findings contribute to the literature by integrating governance, financial, and ESG dimensions, offering practical implications for enhancing corporate transparency and aligning strategies with the UN 2030 Agenda
محددات الافصاح عن اهداف التنمية المستدامة